"It only needs to work for one of us": rethinking DIY deaf tech through situated co-design - Huffman, Shuxu, author; Angelini, Robin, author; Kushalnagar, Raja, author; Spiel, Katta, author; ACM, publisher (Colorado State University. Libraries, 2025)
This experience report presents a real-world case in which a Deaf open water swimmer and their hearing kayak partner designed and developed a vibration-based system for attention signaling during long-distance swims. When mainstream accessibility tools failed to meet their needs, they built a lightweight, context-specific solution grounded in Deaf cultural practices and embodied knowledge. Through in-situ use and reflective practice, we examine how this do-it-yourself (DIY) tool emerged from relational design and Deaf-centered philosophy. Rather than offering a generalized solution, this work highlights the value of culturally grounded, small-scale technologies shaped by the lived experience of a Deaf swimmer and their collaboration with a hearing ally. We conclude with a call for research approaches and design platforms that empower Deaf communities to create technologies rooted in their own values, environments, and ways of being.
It only needs to work for one of us: rethinking DIY deaf tech through situated co-design
Keywords: deaf and hard of hearing; assistive technology; DIY; situated design; deaf-hearing collaboration; disability